PENGARUH KOMPETENSI KEPRIBADIAN GURU TERHADAP PRESTASI BELAJAR SISWA DI MTS AR-RIYADH 13 ULU PALEMBANG - Budi Agus Sumantri; Abdullah Idi; Nurlaila Nurlaila (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2019)
This study aims to determine the teacher's personal competency, student achievement, and the effect of teacher personality competency on student achievement at MTs Ar-Riyadh 13 Ulu Palembang. A teacher must have and be aware of the importance of competence teacher training especially personal competence. Many teachers master learning methodology well and have extensive knowledge of material taught, but not with a personality that reflects as a teacher who can be emulated and exemplary in the middle society especially students. This type of research is a type of quantitative research. While secondary data sources are administrative staff, books and school documentation. The population in this study were all students of Ar-Riyadh MTs 13 Palembang Ulu. While the sample of this study was students of class VIII.A which amounted to 34 students. Data obtained by observation, questionnaire and documentation.First, the data is collected, then recapitulated, then analyzed using statistics, namely by using the formula mean, standard deviation, TSR and percentage, and Product Moment. The results of this study are: first, the personality competencies of teachers in Ar-Riyadh MTs 13 Palembang Ulu are categorized as moderate or good enough because of the 34 respondents there were 21 respondents who stated medium (61.76%). Second, student achievement in Ar-Riyadh MTs 13 Palembang Ulu is categorized as moderate or good enough because of the 34 respondents there were 22 respondents who were in the medium category or equal to (64.70%). Third, there is a significant influence between teacher personality competencies on student achievement at Ar-Riyadh MTs 13 Palembang Ulu. Based on the results of statistical analysis that the